Successful agents in destination governance: Task profiles and required skills - Raich, F.; Pechlaner, H.; Volgger, Michael (2012)
To adapt DMOs to current challenges in destination governance, we investigated determinants of DMO success and compared these results with the actual task profiles of Alpine DMOs in a quantitative study. Thereby professionalism, networking capability, resource endowment, strategic leadership and innovation performance revealed to be required skills. By comparing these requirements with the status quo of Alpine DMOs, it becomes evident that they fall especially short of recognizing the critical role of coordination activities, innovative product development and strategic planning.